Strategi Guru Meningkatkan Rasa Percaya Diri Siswa Kelas IV MIN 16 Banjar - Zulaikha, Zulaikha; Huriyah, Huriyah (Jurnal Riset Madrasah Ibtidaiyah, 2025)
Self-confidence is very important for students in character building and potential development. However, based on previous research, there are still many students who lack confidence, there are still many teachers who still cannot develop students' self-confidence. This study aims to determine the strategies used by IPAS teachers in increasing the confidence of grade IV students at MIN 16 Banjar as well as the supporting and inhibiting factors in implementing these strategies. This research uses descriptive qualitative method field research. The subjects of this study were IPAS teachers in grade IV, the head of madrasah, and grade IV students. The object is the IPAS teacher's strategy in increasing student confidence. Data collection techniques through interviews, observation and documentation. Data analysis method; data reduction, data display, and verification. Data validity through triangulation of sources, techniques and time. The results showed that the IPAS class IV teacher strategy used several strategies such as direct learning in the form of questions and answers and assignments as well as interactive learning strategies in the form of discussions and peer teaching. In addition, teachers also use several efforts such as; paying attention to student circumstances, providing emotional support, maintaining good communication with students, providing encouragement to each student skill, and providing tasks and responsibilities. Supporting factors include; discipline, extracurricular activities, learning media, teacher professionalism. As for the inhibiting factors; family environment, community, and smartphone.